2018
DOI: 10.1016/j.cep.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing mixing quality in a T-shaped micromixer for different fluids properties through numerical simulation

Abstract: Microreaction engineering enables new strategies in process intensification. A precise analysis of local mass transfer and hydrodynamics in micromixers for different flow regimes are strongly needed for a complete understanding the processes occurring. One of the simplest in the manufacture, but at the same time, quite effective T-shaped micromixer was used for numerical investigation and analyzing the mixing quality and flow regimes as well as the influence of different fluids properties on this parameters. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…It was shown in [14][15][16][17][18][19][20][21][22] that the value of the critical Reynolds number depends on the thermophysical properties of mixing fluids. Thus, it was found that as the fluids viscosities ratio increases the critical Reynolds number increases too, but such value doesn't depend on the fluids densities ratio.…”
Section: Figure 1 the Geometric Configuration Of The Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in [14][15][16][17][18][19][20][21][22] that the value of the critical Reynolds number depends on the thermophysical properties of mixing fluids. Thus, it was found that as the fluids viscosities ratio increases the critical Reynolds number increases too, but such value doesn't depend on the fluids densities ratio.…”
Section: Figure 1 the Geometric Configuration Of The Taskmentioning
confidence: 99%
“…Thus, it was found that as the fluids viscosities ratio increases the critical Reynolds number increases too, but such value doesn't depend on the fluids densities ratio. Also, the influence of the rheology of the mixing fluids on the shift of flow regimes in T-shaped micromixer [19,21,22] was pointed out.…”
Section: Figure 1 the Geometric Configuration Of The Taskmentioning
confidence: 99%
“…The numeric technique used in this paper and the results of its testing are described in detail in the papers [23][24][25]. To solve the system of nonlinear differential Equations (1)-(5), we used the finite-volume method (FVM) [36,37].…”
Section: Mathematical Model and Numerical Computation Methodsmentioning
confidence: 99%
“…During the conducted computations, the PD and the ME were calculated. To quantify the mixing efficiency, the parameter M = 1 − (σ/σ 0 ) 0.5 was used [20][21][22][23][24][25]41,42], where…”
Section: Mathematical Model and Numerical Computation Methodsmentioning
confidence: 99%
“…One of the most studied geometries is the T-shaped micromixer, in which the inlets perpendicularly join the mixing channel. Such geometry has been largely investigated numerically, highlighting the presence of both steady (stratified, vortex and engulfment, or steady asymmetric) regimes [13][14][15][16][17][18][19] and unsteady (asymmetric and symmetric time-periodic) regimes. [20][21][22] In particular the unsteady regimes were firstly discovered numerically, [14,20] and only subsequently they were observed experimentally.…”
Section: Introductionmentioning
confidence: 99%